ANALISIS KETERAMPILAN ABAD 21 SISWA IPA FASE D DI SMP N 40 PADANG - Dea Rahmi Sya’bani; Ade Dewi Maharani; Erismar Amri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The learning process at SMP N 40 Padang does not fully implement critical thinking skills as seen from when the teacher gives practice questions to students. Collaboration skills in the group learning process of students are still not able to express ideas, so that in group discussion activities only a few students are active in the discussion. Meanwhile, in terms of communication skills, students are not yet able to communicate well, seen from communicating the results of group work, there are still students who refuse to represent the group moving forward. The purpose of this research is to determine the 21st century skills of class VII phase D students in biology science learning at SMP N 40 Padang.This type of research is descriptive research. The population in this study were all class VII students at SMP N 40 Padang, totaling 156 students. The sample taken was 45 students using random sampling techniques. The instruments used are selected tests (questions) and observation, collaboration and communication sheets. Research uses validity and reliability to see the results of student abilities. Meanwhile, the analysis used uses the Microsoft Excel application which is adjusted using formulas in data analysis techniques. Based on research conducted at SMP N 40 Padang. The results of this research show that the average 21st century skills of students at SMP N 40 Padang is 62.63 with high criteria. With the average values obtained respectively 30.46% with sufficient criteria, 70.69% with high criteria, 75.23% with high criteria and 74.14 with high criteria. So it can be concluded that students' 21st century skills in science learning at SMP N 40 Padang are categorized as high.